EAR LEARNING MODEL: INOVASI PENDIDIKAN RESILIENSI BANJIR BERBASIS ADAPTASI SOSIAL DI SMA PEMBANGUNAN LABORATORIUM UNP - Vany Vadilla; Ernawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: (1) describe the implementation of flood resilience learning through the application of the EAR Learning Model, (2) examine the effect of applying this model on improving students' understanding of flood resilience, and (3) determine the application of social adaptation among students in the flood-prone environment of SMA Pembangunan Laboratorium UNP. This study used a quasi-experimental method with a quantitative approach. Sampling was conducted using purposive sampling techniques with participants from class XI F 1 as the experimental class given the EAR Learning Model treatment and class XI F 2 as the control class with the conventional model. The research instruments included observation, tests (pre-test and post-test), questionnaires, and documentation. The results showed that learning through the EAR Learning Model was carried out in three main stages: (1) Education to increase understanding of flood resilience through learning materials and videos, (2) Adaptation to train students to adjust to environmental changes through role-playing activities, and (3) Resilience by encouraging students' active participation in creating flood mitigation and adaptation messages. The post-test results showed that the average score for the experimental class was 92.7, higher than that of the control class, which was 82.4. The Paired Sample T-test showed a significance level of 0.001 < 0.05, so Ho was rejected and Ha was accepted. This proves that there is a significant difference before and after the model is implemented. In addition, the level of social adaptation of students in flood-prone areas is relatively high in their daily social interactions. These findings indicate that the EAR Learning Model is effective in improving students' understanding of flood resilience and social adaptation.